Cercyon (Cercyon) unipustulatus Nakane 1982 - Ryndevich, Sergey K.; Jia, Fenglong; Fikáček, Martin (Zenodo, 2017)
Cercyon ( Cercyon ) unipustulatus Nakane, 1982 (Figs 9, 12A–D, 13) Cercyon unipustulatus Nakane, 1982: 101. Type locality. Japan, Honshu, Chiba, Abiko. Type material examined. PARATYPE: ♀ (EIHU): ʻRiv. Tone, Abiko (Chiba), 21.IV.1968, coll. M. Shimoi, Nakane coll., Sehu Japan, 1999, 0000030762, Sys.Ent., Hokkaido Univ., Japanʼ [SEHU]. [Comment: This paratype is listed with slightly different data in the original description: Abiko (Tonegawa), 21.iv.1968, M. Shimoi leg.] Additional material examined. JAPAN: KYUSHU: 1 spec. (KMNH): Fukuoka Pref., Tagawa-shi, Urano, 19.vi.1958, at light, Y.Takakura leg., Y. Minoshima det. 2017. RUSSIA: AMUR OBLAST: 1 spec. (ZISP): Tarbogotay, second half of vi.1910. PRIMORSKY KRAI: 1 spec. (CSR): Primorskiy kray, Shkotovskiy r-n, d.[Shkotovsky district], Lukyanovka, 1.ix.1992, A.O. Lukashuk leg.; 5 spec. (CAP, CSR): Lazovskiy zap-k [Lazovskiy Nature Reserve], Sokolovka, na svet [at light], 16.viii.2005, Yu. Sundukov & V. Shokhrin leg.; 1 spec. (CAP): Lazo, 7–13.viii.2005, V. Shokhrin & Yu. Sundukov leg.; 1 spec. (CAP): s. [vill.] Lazo, na svet [at light], 7–8.viii.2005, Yu. Sundukov leg. SAKHALIN OBLAST: 1 spec. (MPU): Kunashir, cordon Аlekhinskiy, 7.vii.2015, Yu. Sundukov & L. Sundukova leg. Published records. RUSSIA: PRIMORSKY KRAI: Chernye Gory, Venedivnovo [likely misspelled form of “Venevitinovo”] (HEBAUER 1995); Lazovsky Nature Reserve (PROKIN 2009). JAPAN: Honshu: Chiba Pref., Abiko (Tonegawa) (NAKANE 1982). Diagnosis. Head black, without pale preocular spot; pronotum black with narrowly pale lateral margins; elytra reddish-yellowish with big black pentagonal sutural spot in the middle of elytra; sutural interval completely black or dark brown; maxillary palpi yellowish to brownish-yellow; elytral intervals flat, very slightly convex in apical part; mesoventral plate narrowly elongate, ca. 4.0–5.2× as long as wide; metaventrite without femoral lines; fifth ventrite not emarginate apically; paramere narrow near base, slightly concave on outer margin, apex almost straight with setae; median lobe widest near base, triangular apically; sternite 9 very narrowly rounded apically, with 2 very short subapical setae. Redescription. Form and color. Body elongate oval (Fig. 9A), length 2.4–3.3 mm, width 1.4–1.9 mm. Head black. Pronotum black with narrowly pale lateral margins, anterior margin very narrowly pale, base very narrowly pale near posterolateral angles. Scutellum brown or dark brown. Elytra reddish-yellowish with big black pentagonal sutural spot located in the middle of elytra; sutural interval completely black or dark brown. Epipleuron reddish-yellowish. Antennae yellowish except for darker club. Maxillary palpomeres yellowish, reddish-yellow to brownish-yellow. Ventral surface black or dark brown, posterior margins of abdominal ventrites yellowish or brownish. Legs brownish-yellow to reddish-brown. Head. Clypeus with dense, moderately coarse punctures, interstices without microsculpture. Anterior margin of clypeus with narrow bead. Frontoclypeal suture undetectable. Frons without microsculpture on interstices. Eyes small, somewhat protruding, interocular distance ca. 6.1–6.3× the width of one eye in dorsal view. Mentum glabrous, ca. 1.6–1.7× as wide as long, densely and coarsely punctate. Antennae with 9 antennomeres, scapus ca. 1.3–1.4× as long as antennomeres 2–5 combined, club compact. Maxillary palpomere 2 strongly swollen, palpomere 4 almost symmetrical, equal to palpomere 3 in length. Thorax. Elytra and pronotum without hairs. Pronotum ca. 2.1–2.2× as wide as long. Pronotal punctation similar to that on head. Lateral margins of pronotum with narrow bead overlapping anterior and posterior corners, anterior and posterior margin without rim. Prosternum with strong longitudinal carina medially; antennal groove distinct, moderately large, rounded laterally. Mesoventral plate narrowly elongate, ca. 4.0–5.2× as long as wide, almost parallel-sided in posterior two thirds, strongly narrowing in anterior third (Fig. 9F). Metaventrite with raised glabrous, sparsely punctate median pentagonal area, anteriorly protruding towards mesoventral plate; femoral lines absent. Elytra with ten punctate striae, striae 1–9 impressed and reaching base, stria 10 very short. Intervals flat anteriorly, slightly convex in apical part; ground punctures on intervals very fine. Humeral bulge indistinct. Epipleura flat, horizontal. Femora with sparse and shallow punctures ventrally, with distinct tibial groove. Tarsi with densely arranged whitish setae ventrally, first metatarsomere about as long as metatarsomeres 2–3 combined. Abdomen. Abdomen with five ventrites, first ventrite distinctly longer than others, ca. 2–2.2× as long as second ventrite, bearing distinct median longitudinal carina, fifth ventrite arcuate, not emarginate apically. Male genitalia (Figs 9B–D). Phallobase slightly longer than parameres, asymmetrical basally. Paramere narrow near base, slightly concave on outer margin, apex membranous, almost straight, bearing setae. Median lobe widest proximal to midlength near base, strongly narrowing apically, basal ароdemes long; lateral margins with very short setae in apical part, apex obtusely pointed; gonopore moderately large, situated subapically. Median projection of sternite 9 very narrowly rounded apically, bearing 2 very short subapical setae, median portion shorter than lateral struts. Variation. Form and size of sutural spot are variable (Figs 12A–D). Pale colored specimens have very vaguely visible small brownish spots near front margin of eyes. Biology. Polysaprophage, inhabiting decaying organic material (NAKANE 1982, SHATROVSKIY 1989). The majority of specimens were collected in cow excrements. Cercyon unipustulatus flies to light. Distribution. Cercyon unipustulatus is endemic in the southern part of Russian Far East (Amur Oblast, Primorsky Krai, Kuril Islands) and for Japan. In northern part of its range it co-occurs with the similar C. unipunctatus with which it can be even syntopic (found together). : Published as part of Ryndevich, Sergey K., Jia, Fenglong & Fikáček, Martin, 2017, A review of the Asian species of the Cercyon unipunctatus group (Coleoptera: Hydrophilidae: Sphaeridiinae), pp. 535-576 in Acta Entomologica Musei Nationalis Pragae (Acta. Ent. Mus. Natl. Pragae) (Acta. Ent. Mus. Natl. Pragae) 57 (2) on pages 560-563, DOI: 10.1515/aemnp-2017-0089, http://zenodo.org/record/5318472 : {"references": ["NAKANE T. 1982: New or little-known Coleoptera from Japan and its adjacent regions. XXXV. Report of Faculty of Science, Kagoshima University (Earth Science & Biology) 15: 101 - 111.", "HEBAUER F. 1995: Bekannte und neue Hydrophiloidea aus Ostsibirien (Col.). Entomologische Nachrichten und Berichte 39: 29 - 36.", "PROKIN A. A. 2009: Family Hydrophilidae. Pp. 110 - 112. In: STOROZHENKO S. YU. (ed.): Insects of Lazovsky Nature Reserve. Dalnauka, Vladivostok, 464 pp (in Russian).", "SHATROVSKIY A. G. 1989. Hydrophilidae. Pp. 264 - 293. In: LER P. A. (Ed.): Opredelitel' nasekomykh Dal'nego Vostoka SSSR v shesti tomakh. Vol. 3. Zhestkokrylye, ili zhuki (part 1). Nauka, Leningrad, 572 pp."]}